2014
DOI: 10.1152/ajpgi.00447.2013
|View full text |Cite
|
Sign up to set email alerts
|

Water-perfused esophageal high-resolution manometry: normal values and validation

Abstract: Water-perfused high-resolution manometry (HRM) catheters with 36 unidirectional pressure channels have recently been developed, but normal values are not yet available. Furthermore, the technique has not been validated and compared with solid-state HRM. We therefore aimed to develop normal values for water-perfused HRM and to assess the level of agreement between water-perfused HRM and solid-state HRM. We included 50 healthy volunteers (mean age 35 yr, range 21-64 yr; 15 women, 35 men). Water-perfused HRM and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
58
2
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 12 publications
5
58
2
1
Order By: Relevance
“…One other study, conducted by Kessing et al ., directly compared a solid‐state to a water‐perfused HRM system . In this study only small differences in outcome measures, such as the Chicago Classification metrics, were found.…”
Section: Limitations and Advantages Of Solid‐state And Water‐perfusedmentioning
confidence: 78%
See 1 more Smart Citation
“…One other study, conducted by Kessing et al ., directly compared a solid‐state to a water‐perfused HRM system . In this study only small differences in outcome measures, such as the Chicago Classification metrics, were found.…”
Section: Limitations and Advantages Of Solid‐state And Water‐perfusedmentioning
confidence: 78%
“…Despite multiple factors influencing normative values, the Chicago Classification is still applicable in most situations. This is even the case when using a higher sensor interval of 2 cm in segments outside the esophagogastric junction, or to some degree when using a type of water‐perfused catheter . However, there were certain flaws in the criteria for hypercontractility and the criteria looking at break size in the 2012 version of the Chicago classification, which have now been addressed in the third version.…”
Section: Discussionmentioning
confidence: 99%
“…The first HRM classification of esophageal motor disorders described the normative esophageal pressure metrics exclusively based on measurements with the Manoscan ™ system . Comparative studies with other HRM systems have only shown moderate to good agreement between various HRM systems, and substantial differences exist in some of the commonly used normative pressure metrics . Currently, it is unknown if other available HRM systems manifest other limitations in accuracy of their pressure measurement.…”
Section: Discussionmentioning
confidence: 99%
“…The following manometric, impedance, and pH‐metric parameters were collected from patients with EGJOO: basal or resting pressure of the LES (LES‐RP) (normal values: 10–35 mmHg), resting pressure of the UES (UES‐RP) (normal values: 34–104mmHg), integrated relaxation pressure (IRP) (normal values IRP4s: <18 mmHg), intrabolus pressure (IBP) (normal values: <12 mmHg), pressurization presence or absence, contractile front velocity (CFV) (normal values: 3.0–6.6 cm/s), distal contractile integral (DCI) (normal values: 450–8000 mmHgm.s.cm), peristaltic defects (normal values: <5 cm), distal latency (DL) (normal values: >6.2 s), esophageal transit: complete (CET) or incomplete (IET) (we considered as normal a complete bolus clearance in at least 70% of liquid swallows), and pathological acid gastroesophageal reflux (GER) with the DeMeester score (normal values: <14.72)…”
Section: Methodsmentioning
confidence: 99%
“…These normal values (thresholds) used are based on the Chicago Classification, except the cut‐offs of technology‐specific measurements such as IRP, DL, CFV, and IBP that are based on the recently defined thresholds by Kessing et al ., for water‐perfused esophageal HRM, similar technique used in this study, and similar thresholds to those recently published by our lab, as the Chicago Classification values are set for Solid‐state HRM. Commonly accepted thresholds were used as reference values for esophageal sphincters resting pressures, esophageal bolus transit, and acid exposure, as these measurements are not included under the Chicago Classification.…”
Section: Methodsmentioning
confidence: 99%